Hydrokinetic energy harnessing technologies: a review - Wan Ismail, Ibrahim; Mohd Rusllim, Mohamed; R. M. T. R., Ismail; Leung, P. K.; Xing, W. W.; A. A., Shah (Elsevier Ltd, 2021)
Energy harnessing from hydrokinetic systems has been explored over several centuries. With advancements in the technology in last decade, and the intermittent nature of other technologies for energy harvesting, interest in harnessing energy from water-based hydrokinetic systems has amplified. This paper reviews and studies the state-of-the-art of these systems in sea- and river-based applications. The history of development, working principles, different turbines classifications, and research prospects and opportunities are reviewed and discussed. We also conduct a survey of currently available commercial technologies. Elements of the design that need to be enhanced are presented in detail, along with further research prospects in areas related to the technology.